Geography of public service delivery in rural Ethiopia - Abate, Gashaw T.; Dereje, Mekdim; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2019)
Remote areas are often characterized by lower welfare outcomes due to economic disadvantages and higher transaction costs for trade. But their worse situation may also be linked to worse public service delivery. Relying on large household surveys in rural Ethiopia, we explore this by assessing the association of two measures of remoteness – (1) the distance of villages and primary service centers to district capitals and (2) the distance of households to service centers (the last mile) – with public service delivery in agriculture and health sectors. In the agriculture sector, we document statistically significant and economically meaningful associations between exposure to agriculture extension and the two measures of remoteness. For health extension, only the last mile matters. These differences between the two sectors could be due to the fact that more remote villages tend to have fewer agriculture extension workers who also put in fewer hours than their peers in more connected areas. This does not apply in the health sector. These findings provide valuable inputs for policymakers aiming to improve inclusiveness in poor rural areas.